Integrated Development and Preservation of Kimpulan Temple Based on Public-Private Partnership - Utami, Wahyu; Mutaqi, Ahmad Saifudin; Salura, Purnama; Lake, Reginaldo Christopori (Departement of Architecture, Universitas Islam Indonesia, 2025)
Conventional preservation of temples often faces challenges related to funding, management, and utilization of sites, resulting in incomplete conservation efforts. This study aims to explore the successful preservation of Candi Kimpulan through the Public-Private Partnership (PPP) approach model. The PPP model is expected to address these challenges by optimizing resources and creating synergy between the government, private universities, and the community. The theoretical basis emphasized is the Public-Private Partnership (PPP) approach as a collaboration model between the government, private institutions, and the community to support the sustainable preservation of cultural heritage by optimizing the function, form, and meaning of cultural sites. This qualitative research utilizes a case study method to analyze the impact of PPP on the function, form, and meaning of the preservation of Candi Kimpulan. The findings indicate that the PPP model implemented in the development of the Universitas Islam Indonesia (UII) Library and Museum building, integrated with the restoration of Candi Kimpulan, successfully created a progressive preservation zone, functional space reconciliation and enhanced the site's cultural significance. Collaboration among stakeholders in this project ensures the sustainability of cultural preservation, creating multifunctional spaces that support education, research, and maintenance. In conclusion, the PPP approach has proven effective in supporting sustainable cultural heritage preservation, making Candi Kimpulan a successful model for other preservation projects. Keywords: Conservation; Integrated Development; Public-Private Partnership